The Behavioural Biology of Dogs - Jensen, Per (CABI, 2014)
In this first part of the book, the dog is placed in context amongst its zoological relatives, and in relation to its domestication history. The first chapter outlines the modern view on the zoological systematics of carnivores and canids in particular. Here, the reader will find an exciting account of fossil and present traits which allows the dog to be placed within the greater picture of closely related canids. Of course, the dog is a domesticated species, and its domestication history has been subject to intense research during the last decade or so. Here, modern molecular genetics offers tools which have allowed biologists to give their pictures of how, where and when domestication started, complementing the traditional picture offered mainly by archaeologists. Some aspects of this new picture are truly stunning and require that we revise large parts of our traditional views on how domestication began.